The British in India and their domiciled brethren - Mizutani, S (2004)
﻿ This DPhil dissertation aims to delineate an ambivalent construction of 'Britishness' in late British India by paying special attention to certain discourses and practices that regulated the lives of both colonial elites and of their impoverished and/or racially mixed kin. Peculiar racial self-anxieties of the colonial ruling classes, - namely those over hygienic / sexual degradation and cultural hybridisation, the increased presence of indigent and/or racially mixed white populations, and the undesired consequences of the last - are examined thorough a close and analytically coherent analysis of colonial representations and practices. An important feature of this research is to bring the internal-cum-class distinctions of metropolitan society to the fore in order to circumscribe a peculiarly class-specific constitution of British racial identity in the colonial context. Broadly speaking, in two related senses can the (re)production of white racial prestige in the British Raj be regarded as a class-conditioned phenomenon. First of all, colonial Britishness can be said to have been characterised by class because not all persons or groups of British descent living in the colony were recognised as 'European enough': only those from the upper or middle classes were considered as so 'European' as to be capable of ruling the 'subject races' of India. The remaining people of British racial origins, including the so-called 'poor whites', the 'domiciled Europeans' (those whites permanently settled in India), and the mixed-decent 'Eurasians', were not regarded as 'British enough' (although they were not seen as 'Indian', either). Especially, 'domiciled Europeans' and 'Eurasians', often collectively referred to as 'the domiciled class', were not treated as 'British' but only as 'Native' in socio-legal terms: the 'domiciled' differed from 'Indians' in terms of racial and cultural identification, but were supposed to be no higher than the latter by constitutional status and socio-economic standard. Secondly it was because of its recourse to 'bourgeois philanthropy' that the construction of Britishness in late British India may be said to have been bound by aspects of Victorian or Edwardian class culture. Although the British excluded their domiciled brethren from the sphere of their social and economic privileges, the former also 'included' the latter within limited frames of philanthropic and educational care. For, their exclusion from the elite white community notwithstanding, the domiciled were still regarded as one part of the European (as opposed to Indian) body politic. Thus the colonial authorities feared that an unregulated destitution of 'poor whites', domiciled Europeans, and Eurasians might present itself as a political menace to the prestige of the British race as a whole: in a sense, the authority of Britishness also depended on how 'European pauperism' could be solved before it had disorderly effects on the colonial hierarchies of race and class. It was in this context that the philanthropic management of pauperism emerged as a negative but no less unimportant measure for reproducing British prestige in the colonial context. And central to this was a specific, colonial application of a politics of class that the bourgeoisie played against the indigent and various 'unfit' populations in the metropole.